A noninvasive diagnostic approach to retrospective donor HLA typing in kidney transplant patients using urine - Bach, Christian; Knaup, Karl; Herrmann, Markus; Krumbiegel, Mandy; Pfister, Frederick; Büttner-Herold, Maike; Steffen, Martin; Zecher, Daniel; Lopau, Kai; Schneider, Karen; Dieterle, Anne; Amann, Kerstin Ute; et al. (Transplant International, 2021)
Antibody-mediated rejection (AMR) is a major obstacle to long-term kidney transplantation. AMR is mostly caused by donor specific HLA antibodies, which can arise before or any time after transplantation. Incomplete donor HLA typing and unavailability of donor DNA regularly preclude the assessment of donor-specificity of circulating anti-HLA antibodies. In our centre, this problem arises in approximately 20% of all post-transplant HLA-antibody assessments. We demonstrate that this diagnostic challenge can be resolved by establishing donor renal tubular cell cultures from recipient´s urine as a source of high-quality donor DNA. DNA was then verified for genetic origin and purity by fluorescence in situ hybridization and short tandem repeat analysis. Two representative cases highlight the diagnostic value of this approach which is corroborated by analysis of ten additional patients. The latter were randomly sampled from routine clinical care patients with available donor DNA as controls. In all 12 cases, we were able to perform full HLA typing of the respective donors confirmed by cross-comparison to results from the stored 10 donor DNAs. We propose that this noninvasive diagnostic approach for HLA typing in kidney transplant patients is valuable to determine donor specificity of HLA antibodies, which is important in clinical assessment of suspected AMR.
CRIS-Team Scopus Importer:2021-06-25
Keywords: antibody-mediated rejection; HLA typing; HLA-antibody post-transplantation; rejection